Manajemen Pasca Bencana Abrasi Di Desa Anak Setatah Kecamatan Rangsang Barat Kabupaten Kepulauan Mernti - Nur Syazila; Dadang Mashur (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
Anak Setatah village is a village whose land directly faces the malacca straits and Anak Setatah village is a village that often experiences abration due to verry large sea waves. Anak Setatah village is located in the West Tributary District, Meranti Archipelago Distric. This study aims to determine post-disaster managemen In Anak Setatah Village. The research uses descritive qualitative method becauseit is done by interviews, obsevation, and documentation. The results showed that post-abrasion management was quite good, but there werw still many shortcomings that needed to be corrected, such as goverment budgets,illegal logging and how to prevent the seed from being washed away by the waves during high waves. In addition, there is an inhibiting factor for post-abrasion management, namely the lack of public awareness of the importance of mangrove forest for future sustainability. Mangroves are plants that are usually planted by the community in Anak Setatah village to prevent very severe abrasion. Very severe abrasion occurred in the village of Anak Setatah. This research was conducted by going to the field, seeing directly and interviewing the village community of Anak Setatah. The inhibiting factor of this research in the lack of buged from the government and public awareness. However, whit post –abrasion disaster management in Anak Setatah village, this very severe abrasion is no longer there and new soil is growing due to the grip of the mangrove roots.